Calcaneocuboid joint dislocation: A case report - (:unkn) unknown (American Podiatric Medical Association, 2014)
Tarsal bone dislocation is a rare entity. It is usually undiagnosed in the emergency department. We present the case of a 44-year-old man who was diagnosed as having calcaneocuboid joint dislocation in the emergency department. The dislocation was reduced in the emergency department, and a below-the-knee cast was applied. Successful clinical and radiologic results were obtained during follow-up. In this case, unlike the previous reports in the literature, conservative management succeeded in the treatment of calcaneocuboid joint dislocation. © 2014, American Podiatric Medical Association, Inc.